AB0613 Pulmonary artery diameter and pulmonary hypertension in systemic sclerosis. (15th June 2017) - Schreiber, BE; Denton, CP; Robinson, G; Wells, AU; Keir, G; Sverzelatti, N; Suntharalingam, J; Coghlan, G
Abstract : Background: Systemic sclerosis may be complicated by pulmonary hypertension. CT-determined pulmonary artery diameter has been shown to correlate with presence of pulmonary hypertension in idiopathic patients and in interstitial lung disease but not in scleroderma. Objectives: To determine the utility of CT-determined main pulmonary artery diameter (MPAD) for predicting pulmonary hypertension (PH) in 97 patients with systemic sclerosis who had CT chest within six months of right heart catheterisation. Methods: Retrospective review of right heart catheter and CT data done within six months in 97 patients. The CT scans were blindly scored by two radiologists. Results: 97 patients (75 female, 22 male) with systemic sclerosis who underwent CT scan and right heart catheterization were analysed. About 2/3 had the limited subtype (64 limited, 24 diffuse, 6 undefined). Pulmonary hypertension was present in 55 patients (57%) and interstitial lung disease affecting 20% of the lung or more was present in 42 patients (43%). Survival was worse in those with pulmonary hypertension. Median survival was 9.3 years in those without pulmonary hypertension (8.1–10.5) and 4.4 years in those with pulmonary hypertension (2.6–6.2). Presence of interstitial lung disease and pulmonary hypertension were independent predictors of survival. An ROC curve shows area under the curve of 0.864. MPAD threshold of 25 mm or greater has a sensitivity of 98% and a specificity of 33% for the presence of pulmonary hypertension; 30 mm has a sensitivity of 73% and a specificity of 81% for the presence of pulmonary hypertension; 32 mm has a sensitivity of 56% and a specificity of 88% for the presence of pulmonary hypertension and 34 mm has a sensitivity of 35% and a specificity of 98% for the presence of pulmonary hypertension. Survival was worse in those with a MPAD of 30mm or greater, with median survival of 5.5 years (3.8–7.2) compared to survival of 9.3 years (7.9–10.7) in those with MPAD smaller than 30mm. It was not a significant predictor of survival after adjustment for presence of pulmonary hypertension and interstitial lung disease. Conclusions: The CT determined MPAD correlates strongly with the presence of pulmonary hypertension in patients with systemic sclerosis. Disclosure of Interest: None declared